Controlling factors of low resistivity in deep shale and their implications on adsorbed gas content: a case study in the luzhou area - Mugui Liang; Guang Fu; Yinghua Yu; Hongqi Yuan (Scientific Reports)
Abstract Numerous gas-rich, low resistivity shale wells have been discovered in the Luzhou deep shale gas of Sichuan Basin, providing strong evidence that low-resistivity shale also holds significant potential for shale gas exploration. However, existing research has limited understanding of the mechanisms of low resistivity in shale, and the mechanisms by which low-resistivity influences gas content remain unclear. Here, we conducted X-ray diffraction analysis (XRD), total organic carbon (TOC) content, vitrinite reflectance (Ro), low-temperature N2 and CO2 adsorption experiments, methane isothermal adsorption experiments, nano-CT, laser Raman experiment, and well-logging curve to quantality evaluate the low resistivity shale formation mechanisms and explore the factors influencing gas content in low resistivity shale. The resistivity in the Wufeng Formation is 50 Ω·m with an adsorbed gas content of 1.6 m³/t, while in the Longmaxi Formation, the resistivity is 100 Ω·m with an adsorbed gas content of 2.4 m³/t in its first layer. The adsorbed gas content gradually decreases from first layer to fourth layer in Longmaxi Formation, which is related to TOC content, pore structure, clay mineral content. We find that organic matter, pyrite, clay minerals, and formation water are the main factors to cause the low-resistivity shale. A second harmonic peak (G’ peak) appears near 2,700 cm−1 in Wufeng Formation in indicating that organic matter graphitization has occurred and the maturity is significantly higher than that of Longmaxi Formation without the G’ peak. This study enhances our understanding of low-resistivity and adsorbed gas content in deep shale gas.